Quantity Aggregation in Consumer Demand Analysis when Physical Quantities are Observed - Nelson, Julie A. (The Review of Economics and Statistics, 1990)
A method for estimating price and income elasticities from cross section data devised by Deaton (1986, 1987, 1988) makes implicit use of the Hicks' composite commodity theorem. Recognition of this fact allows theoretically rigorous definition of aggregate composite quantities. A comparison of elasticities of Hicks' composite with elasticities of simple physical quantity measures for the Ivory Coast and the United States demonstrates that use of physical quantity measures can be severely misleading when commodity heterogeneity is substantial. Copyright 1990 by MIT Press.